The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1806-66902013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Substâncias húmicas e suas relações com o grau de subsidência em Organossolos de diferentes ambientes de formação no Brasil

Abstract: RESUMO -A matéria orgânica do solo é parte de um sistema dinâmico influenciado por vários fatores, incluindo clima, conteúdo e natureza das argilas, uso da terra, sistemas de manejo e drenagem, os quais afetam as taxas de adição e os processos de transformações e evolução dos compostos orgânicos. O objetivo deste trabalho foi quantificar e avaliar a distribuição das frações húmicas em Organossolos de diferentes ambientes e regiões do Brasil, relacionando-os com os processos de subsidência. O teor de carbono (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…According to Orlov (1998), increase in the C stocks of HAF may be an indicator of improvement in the quality of the soil humus or of the increase in biological activity, which promotes the synthesis of more condensed humic substances. Similar results were observed by Ebeling et al (2013); upon evaluating the C stock in humic fractions of diverse samples of Organossolo (Histosol) from different regions of Brazil, they observed that the values of the C HAF /C FAF ratio were greater than 1 and concluded that the environmental conditions favored the stabilization of C in the HAF. In contrast, Leite et al (2003) observed that the C HAF /C FAF ratio was greater in the soil under native vegetation than in the soil under agricultural production systems, explaining that in natural forests, without disturbance of the soil, there is greater polymerization of humic compounds, increasing the proportion of the HAF in relation to the FAF.…”
Section: Carbon Stocks In the Humic Substancessupporting
confidence: 80%
“…According to Orlov (1998), increase in the C stocks of HAF may be an indicator of improvement in the quality of the soil humus or of the increase in biological activity, which promotes the synthesis of more condensed humic substances. Similar results were observed by Ebeling et al (2013); upon evaluating the C stock in humic fractions of diverse samples of Organossolo (Histosol) from different regions of Brazil, they observed that the values of the C HAF /C FAF ratio were greater than 1 and concluded that the environmental conditions favored the stabilization of C in the HAF. In contrast, Leite et al (2003) observed that the C HAF /C FAF ratio was greater in the soil under native vegetation than in the soil under agricultural production systems, explaining that in natural forests, without disturbance of the soil, there is greater polymerization of humic compounds, increasing the proportion of the HAF in relation to the FAF.…”
Section: Carbon Stocks In the Humic Substancessupporting
confidence: 80%
“…Isso ocorre porque a rotação pode promover a ciclagem de nutrientes e melhorar a estrutura do solo (TEJADA; HERNANDEZ; GARCIA, 2008), além de aumentar o estoque de carbono (RIBEIRO et al, 2011;ROSOLEM;CALONEGO, 2013). Diferentes sistemas de manejo influenciam diretamente na quantidade de carbono orgânico dos solos (EBELING et al, 2013;FONTANA et al, 2011;TOMASI;INDA;DICK, 2012).…”
Section: Introductionunclassified
“…The TOC content of the soil depends among other factors on the climate, on the content and nature of the clays, on land use, and on the management and drainage systems(Ebeling et al, 2013). According toMartins et al (2010), water deficit is the main limiting factor in semi-arid environments.…”
mentioning
confidence: 99%